Нож и ствол: [повесть] / Алексей Мальцев - Мальцев Алексей Васильевич (Русский бестселлер, 2002)
Экземпляры: ф.6 (2004) / Инвентарный номер: 47799 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44